Biopsy rate and nonalcoholic steatohepatitis (NASH) in patients with nonalcoholic fatty liver disease (NAFLD). (2nd June 2020) - Gerhardt, Florian; Petroff, David; Blank, Valentin; Böhlig, Albrecht; van Bömmel, Florian; Wittekind, Christian; Berg, Thomas; Karlas, Thomas; Wiegand, Johannes
Abstract: Background: Licensed therapies for nonalcoholic fatty liver disease (NAFLD) do not yet exist, but clinical trials are testing treatment options. Inclusion criteria often require liver biopsy showing fibrosis (F2/3) or cirrhosis (F4) and nonalcoholic steatohepatitis (NASH). However, histological criteria pose a serious obstacle for recruitment. Aims: Characterize the relevance of liver biopsies in the selection of patients with NAFLD. Methods: Patients between 2013 and 2018 with the ICD-10 code K76.0 were analyzed. Fibrosis was defined by the NASH clinical research network (CRN) fibrosis staging system, NASH by a NAFLD activity score (NAS) ≥4. Predictive factors were determined by logistic regression. Results: Liver biopsy was performed in 87/638 (13.6%) patients (49% female, age 52.5 ± 14.0, BMI 30.4 ± 5.9 kg/m 2 ). Fibrosis stage F0/F1/F2/F3/F4 was observed in N  = 7/47/7/17/9, an NAS ≥4 in N  = 27. Fibrosis stage F2/F3 and F4 along with NAS ≥4 was found in 1.7% and 0.5% of cases. Liver stiffness measurement, LSM (OR 2.3 per doubling of value; CI 1.3–4.4, p  = .005) and FIB-4 (OR 2.3 per doubling of value; CI 1.2–4.4, p  = .012) were significant predictors for fibrosis ≥ F2. Predictive factors for NASH were not identified. Conclusion: The biopsy rate in NAFLD patients is low and fibrosis ≥ F2 along with NAS ≥4 only present in a few cases. Transient elastography and FIB-4 are useful to select patients at risk for fibrosis for liver biopsy.